Substrate specificities of two ketosynthases in eukaryotic microalgal and prokaryotic marine bacterial DHA synthases - Kaito Ogata; Riku Nakama; Hiyu Kobayashi; Tomoya Kawata; Chitose Maruyama; Takeshi Tsunoda; Tetsuro Ujihara; Yoshimitsu Hamano; Yasushi Ogasawara; Tohru Dairi (Proceedings of the National Academy of Sciences, 2025)
Highly reducing iterative polyketide synthases (HR-iPKSs) are huge enzyme complexes with multiple catalytic domains that biosynthesize polyketides by intrinsically programmed iterative carbon chain extensions and reductions. Unlike most HR-iPKSs, which possess a single ketosynthase (KS) domain for all carbon chain elongations, polyunsaturated fatty acid (PUFA) synthases contain two KS domains. We previously examined the substrate specificities of two KS domains of prokaryotic marine PUFA synthases with several acyl-ACP intermediates and showed that the two KS domains are utilized differentially depending on the carbon chain length. In this study, we investigated two KS domains in a eukaryotic microalgal DHA synthase, KS A and KS B , which show low similarities to those of prokaryotic marine enzymes, together with almost all the acyl-ACP intermediates. C6-, C12-, and C18-ACPs were exclusively accepted by KS A while KS B utilized C-8. C14- and C20-ACPs. In contrast, both KS A and KS B showed activities against C2-, C4-, and C10-ACPs. A general tendency was observed in which both the prokaryotic KS and the eukaryotic KS recognized the acyl structures in the vicinity of the thioester in ACP substrates except for short-chain substrates.